Charateristics of Gynecological Abnormalities and Types of Urine Diversion at Dr Soetomo Hospital, Surabaya, Indonesia, in Three-Year Period - Soetojo, Soetojo; Nurdin, Ambo Tuwo (Folia Medica Indonesiana, 2019)
In the case of advanced stage gynecological disorders, most patients have a disturbance in the upper urinary tract. Most patients with uterine cervical carcinoma are already in stage 3B and require urine diversion. The purpose of this study is to find and determine the profile of gynecological disorders that require urine diversion, the type of urine diversion, and urine diverted output in patients with cervical carcinoma. This descriptive analytical retrospective study was conducted at Dr. Soetomo Hospital, Surabaya, Indonesia, between 2012 and 2015. The samples of this study were all patients with gynecological disorders who underwent retrograde DJ stent procedures, underwent ureterocutaneostomy and nephrostomy at the Integrated Central Surgery Building, Dr. Soetomo Hospital, Surabaya, for three years between 2012 and 2015. Data was collected based on the medical record number of patients with gynecological disorders who underwent urine diversion procedures and were recorded in the book on the operation schedule. We find that the most common cause of gynecological abnormalities in kidney obstruction is cervical carcinoma. There are three types of urine diversions used, namely DJ stent, percutaneous nefropyelostomy, and ureterocutaneostomy, with DJ as the most commonly performed. Urine diversion can improve creatinine without being influenced by the type of diversity.